Shock-Induced Decomposition of 1, 3, 5-triamino-2, 4, 6-trinitrobenzene: A Reactive-Force-Field Molecular Dynamics Study. Issue 17 (2016) - Tiwari, Subodh C.; Nomura, Ken-ichi; Kalia, Rajiv; Nakano, Aiichiro; Vashishta, Priya
ABSTRACT: Shock-induced detonation simulation provides critical information about high explosive (HE) materials including sensitivity, detonation velocity and reaction pathways. Here, we report a reactive force-field molecular dynamics simulation study of shock-induced decomposition of 1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB) crystal. A flyer acts as mechanical stimuli to induce shock in the system, which initiates chemical reactions. Reaction pathway study reveals that the detonation process of TATB is distinct from those in Octahydro-1, 3, 5, 7-tetranitro-1, 3, 4, 7-terazocine (HMX) and 1, 3, 5-Trinitro-1, 3, 5-triazacyclohexane (RDX). Unlike the latter HE materials, N2 production in TATB occurs via three different intermolecular reaction pathways. Being an oxygen deficient HE material, a large carbon rich aggregate remains after the reaction.